Results of a phase II randomized controlled clinical trial comparing efficacy of Cabazitaxel versus Docetaxel as second line or above therapy in recurrent head and neck cancer. (December 2017) - Joshi, Amit; Patil, Vijay; Noronha, Vanita; Dhumal, Sachin; Pande, Nikhil; Chandrasekharan, Arun; Turkar, Siddharth; DSouza, Hollis; Shrirangwar, Sameer; Mahajan, Abhishek; Arya, Supreeta; Juvekar, Shashikant; et al.
Highlights: Cabazitaxel was compared with Docetaxel post first-line palliative chemotherapy. Cabazitaxel failed to improve outcomes. Docetaxel had a better disease control rate. PFS and OS were also numerical superior with Docetaxel. Abstract: Background: Cabazitaxel has shown activity in squamous cancer cell lines and in taxane resistant cell lines. Hence we planned a phase 2 study to evaluate the efficacy of cabazitaxel against Docetaxel in recurrent head and neck cancer, post first line treatment. Methods: This was a phase 2, investigator initiated, randomized controlled trial of Docetaxel (75 mg/m 2 ) versus Cabazitaxel (20 mg/m 2 ), in patients with head and neck cancer with ECOG performance status 0–2 who have been exposed to at least one line of chemotherapy, involving a sample size of 92 (46 per group)(CTRI/2015/06/005848). Disease control rate at 6 weeks was assessed and compared using the chi-square test. Results: The disease control rate at 6 weeks was better in the Docetaxel arm over the cabazitaxel arm (52.3% versus 13.6%, p = 0.017). The median progression free survival was 21 days (95% CI 5.28 to 36.72 days) in the cabazitaxel arm versus 61 days (95% CI 21.39 to 100.60 days) in the Docetaxel arm (HR-1.455, 95% CI 0.919–2.304, p = 0.100). The median overall survival was 115 days (95% CI 74.04 to 155.95 days) in the cabazitaxel arm versus 155 days (95% CI 148.6 to 161.40 days) in the Docetaxel arm (HR-1.464, 95% CI 0.849–2.523, p = 0.170). Conclusion: Docetaxel had a superior disease control rate at 6 weeks compared to cabazitaxel.